2019
DOI: 10.1016/j.isci.2019.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interaction of BRCA1 and CREBBP in Murine Hematopoiesis

Abstract: SummaryBoth BRCA1 and CREBBP are tumor suppressor genes that are important for hematopoiesis. We have previously shown that mouse Brca1 is essential for hematopoietic stem cell (HSC) viability. In contrast to Brca1 deficiency, which results in pancytopenia, we report here that Crebbp deficiency results in myeloproliferation associated with an increase of splenic HSCs as well as a lethal systemic inflammatory disorder (LD50 = 86 days). To investigate the interaction of these two proteins in hematopoiesis, we ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(65 reference statements)
1
3
0
Order By: Relevance
“…Use of unspecific or unreliable antibodies for mouse endogenous BRCA1 protein detection occurred in the field in the past three decades. In this study, we found that antibody 287.17 specifically recognizes mouse BRCA1 protein in WB, IP and IF, consistent with reports from recent publications 76 , 77 . We hope our rigorous characterization of BRCA1 antibodies will be helpful to researchers in the BRCA1 field especially those who study BRCA1 in mouse models.…”
Section: Discussionsupporting
confidence: 93%
“…Use of unspecific or unreliable antibodies for mouse endogenous BRCA1 protein detection occurred in the field in the past three decades. In this study, we found that antibody 287.17 specifically recognizes mouse BRCA1 protein in WB, IP and IF, consistent with reports from recent publications 76 , 77 . We hope our rigorous characterization of BRCA1 antibodies will be helpful to researchers in the BRCA1 field especially those who study BRCA1 in mouse models.…”
Section: Discussionsupporting
confidence: 93%
“…Flow samples were analyzed using the FACS Canto RUO analyzer (BD Biosciences). Gating schemes for hematopoietic progenitors were performed as previously described ( 17 , 63 , 64 ) using fluorescence minus 1 control. Complete peripheral blood counts were assessed using the HemaVet HV950 with MULTI-TROL Mouse as an equilibration control (Drew Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…For flow experiments, bone marrow and spleen single cells suspensions were created as described (63). For HSC and progenitor analysis cells were incubated with biotinylated lineage specific antibodies (CD3ε, CD4, CD5, CD8a, CD45R, CD11b, Gr-1, Ter119) and fluorophore-conjugated antibodies against progenitor surface markers (Sca1, c-kit, CD16/32, CD34, CD48, CD150).…”
Section: Hematopoietic Analysismentioning
confidence: 99%
“…Crebbp and Brca1 functionally interact to maintain normal hematopoiesis. Crebbp haploinsufficiency in mice is deleterious for the bone marrow microenvironment, which results in myeloproliferation associated with an increase in splenic HSCs as well as a lethal systemic inflammatory disorder [35,36].…”
Section: The Role Of Crebbp/ep300 In Normal Hematopoiesismentioning
confidence: 99%